AB0517 USE OF POSITRON EMISSION TOMOGRAPHY IN RHEUMATOLOGY PRACTICE. (2nd June 2020) - Özdemir Işik, Ö.; İsgören, S.; Yazici, A.; Cefle, A.
Abstract : Background: Positron emission tomography (PET), which is widely used in oncology, has recently been used as a guide in the diagnosis of vasculitis and activity monitoring. Objectives: In this study, we aimed to present the desired PET results for the preliminary diagnosis of vasculitis and follow-up. Methods: PET results requested from the rheumatology outpatient clinic between 2012–2019, clinical findings of patients and other imaging methods were reviewed and evaluated retrospectively. Results: PET results were achieved of 36 patients (47% male, 53% female). Constitutional symptoms were present in 67% of the patients with a mean age of 51 ± 18 years. The mean erythrocyte sedimentation rate (ESR) was 49 ± 33 mm/h, CRP was 46 ± 33 mg / L, and leukocyte value was 8.8 ± 3 K / mm 3 at the onset of the disease. While 60% of 25 patients with large vessel vasculitis had a murmur in at least one affected area, 48% had no pulse. While 78% of all patients had a finding in favor of vasculitis in non-PET imaging, this rate was 39% in PET(Table-1). Although the most commonly used imaging method is conventional angiography, recently CT and MR angiography have been requested more frequently. Only 32% of patients who are signs of vasculitis in other images had vasculitis in PET. PET was requested with preliminary diagnosis of vasculitis in 24 patients and vasculitis was detected in 46% of the cases. In twelve of the patients with vasculitis had 25% activity involvement in the desired PET for the presence of activation. In 5 of 8 patients with a pre-diagnosis of vasculitis who had no evidence of vasculitis in any other imaging modalities, the involvement of vasculitis was detected in the PET, and the diagnosis was confirmed Before PET, 44% of the patients had not received steroid treatment. In this group, 63% of patients who did not take steroids, had vasculitis findings in PET. In steroid receiving group, the rate of PET involvement was 20%. Presence of vasculitis in PET was significantly higher in patients who did not receive steroid prior to PET (p = 0.009)(Table-2). The mean duration of steroid intake before PET was 28 ± 69 months. Conclusion: PET is an increasingly used imaging technique in rheumatology practice. The main advantage of PET is that it recognizes other pathologies such as infection and tumor in patients with systemic symptoms. Disadvantage is an expensive test, high radiation rate and misinterpretation of atherosclerosis. Vasculitis is a group of diseases that require rapid diagnosis and treatment. Because of the indisputable contribution of imaging methods at the diagnosis stage, PET was emphasized in this study References: [1]Dejaco C, et al. EULAR recommendations for the use of imaging in large vessel vasculitis in clinical practice Ann Rheum Dis 2018;77:636–643. Disclosure of Interests: None declared